2016
DOI: 10.1016/j.ijheh.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical quality and regulatory compliance of drinking water in Iceland

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…In Spain, median concentrations were 3.5 mg/L NO 3 (range: 0.4−66.8) in 108 municipalities in 2012 [ 22 ], and 4.2 mg/L (range: <1−29) in 11 provinces in 2010 [ 23 ]. Levels in other countries included a median of 0.18 mg/L (range: <0.02−7.9) in Iceland in 2001−2012 [ 24 ], a mean of 16.1 mg/L (range: 0.05−296 mg/L) in Sicily, Italy in 2004−2005 [ 25 ] and a range from undetected to 63.3 mg/L in Deux-Sèvres, France in in 2005−2009 [ 26 ].…”
Section: Drinking Water Nitrate Exposures In the United States Andmentioning
confidence: 99%
“…In Spain, median concentrations were 3.5 mg/L NO 3 (range: 0.4−66.8) in 108 municipalities in 2012 [ 22 ], and 4.2 mg/L (range: <1−29) in 11 provinces in 2010 [ 23 ]. Levels in other countries included a median of 0.18 mg/L (range: <0.02−7.9) in Iceland in 2001−2012 [ 24 ], a mean of 16.1 mg/L (range: 0.05−296 mg/L) in Sicily, Italy in 2004−2005 [ 25 ] and a range from undetected to 63.3 mg/L in Deux-Sèvres, France in in 2005−2009 [ 26 ].…”
Section: Drinking Water Nitrate Exposures In the United States Andmentioning
confidence: 99%
“…Assessment of ambient water quality determines its use for humans and ecological purposes. 1,2 Anthropogenic activities make the surface and ground water highly polluted 3 owing to the fact that surface water is extensively being used in industrial activities, agriculture sector, domestic and municipal facilities. As clean water is highly demanded, it can be derived from various sources but unfortunately, surface waters most often have threat of begin polluted and their low quality status leads to public health issues.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, there has been a significant reduction in the presence of the fecal indicator E. coli in drinking water (EC, 2014(EC, & 2016. However, many studies have shown that the water quality at small water supplies is poorer than for large water supplies and information on their status is often lacking (EC, 2014;Beaudeau et al, 2010;Hulsmann, 2005;Pitkänen et al, 2011;Hendry & Akoumianaki, 2016;Gunnarsdottir et al, 2017a;Gunnarsdottir et al, 2016;Gunnarsdottir et al, 2015). Sixty-five million European citizens, or around 8%, are estimated to be served by small water supplies and two million are without water service (Klaassens et al, 2016;Hulsmann, 2011).…”
Section: Introductionmentioning
confidence: 99%